Improving primary care : - Bodenheimer, Thomas. (Lange Medical Books/Mcgraw-Hill, 2007)
Practice Improvement: The Primary Care Source Book offers frank appraisals and concrete recommendations for primary care practitioners on how to meet the huge, stress-inducing, challenges that they face on a daily basis. The authors offer innovative approaches and suggestions to dealing with primary care issues ranging from the latest electronic technologies to non-traditional options for the patient-physician encounter.